Modeling of production process by the method of works maximum approximation - Dyachenko, Evgen; Zyma, Oleksandr; Pahomov, Roman (Academic journal Industrial Machine Building Civil Engineering, 2020)
The work is devoted to mathematical modeling of production processes. Existing methods of production processes modeling are analyzed. Calculated workflow schemes are proposed when planning the manufacturing process by maximizing work approximation. The dependences of the time parameters calculation and the conditions of the proposed calculation schemes application are given. The method of the time parameters calculation of production processes execution by the method of works maximum approximation is offered. The procedure of calculation and construction of production processes calendar schedule is given. The advantages of the proposed methodology in comparison with existing modeling methods are analyzed
Keywords: mathematical modeling of production; method of works maximum approximation; calculation schemes; calculation of time parameters of production processes execution; calendar schedule